Improvement of damping properties in laser processed superelastic Cu-Al-Mn shape memory alloys. (15th May 2016) - Oliveira, J.P.; Zeng, Z.; Omori, T.; Zhou, N.; Miranda, R.M.; Fernandes, F.M. Braz
Abstract: Cu-based shape memory alloys may be a prime candidate to replace NiTi in specific applications due to their reduced cost and excellent superelasticity. Superelastic Cu-Al-Mn alloy is currently being studied for potential applications as damping systems in seismic devices. However, joining techniques are often required to obtain complex shapes to be incorporated into multi-functional systems. In this study, the effect of post-weld laser processing was investigated in a laser welded superelastic Cu-17Al-11.4Mn (at.%) alloy and the mechanical properties were assessed. It was observed that post-weld laser processing increased the alloy tensile strength to almost the double of the as-welded material while the capability to absorb energy during mechanical cycling increased up to 1.7 times. Thus, laser processing was seen as a suitable technique to improve mechanical properties of welded CuAlMn alloys, supporting the use of these materials in applications where both strength and energy absorption are required, such as in seismic applications. Highlights: Post-weld laser processing of laser welded superelastic Cu-17Al-11.4Mn (at.%) wires was performed. The tensile strength of the post welded wires was doubled over that of both base and as-welded materials. The energy absorption during mechanical cycling increased by 1.7 times compared to the base and as-welded materials. Superelasticity was preserved after post-weld laser processing. Stabilized hysteretic response after the 2 nd mechanical cycle and an absorbed energy similar to that of the base material. Graphical abstract: